2017
DOI: 10.1186/s40852-017-0071-2
|View full text |Cite
|
Sign up to set email alerts
|

The features of economic growth in the case of Latvia and Lithuania

Abstract: Innovation based growth and development is a hot topic in all economies of the world. Openness of mind, openness of businesses and openness of innovation are the key characteristics and success factors of the global world today. Growth and development strategies are becoming smarter transforming economy towards creation of higher added-value products, services and more effective use of resources. Such a high-priority aim may be achieved by R&D activities, which raise the innovation growth and, positively influ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…It can therefore be concluded that the initially lower level of development is conducive to higher dynamics of GDP growth. The variables found in the second and third positions of the ranking, that is, X 2 , gross national savings, and X 12 , gross fixed capital formation, respectively, refer to a similar subject, which can have a considerable impact on the dynamics of economic growth, both theoretically and in practice (Matuzeviciute and Butkus [69], Danileviciene and Lace [70]). Gross fixed capital formation directly demonstrates the proportion of GDP that is further invested, and the gross national savings, understood in the Keynesian approach, can be also ultimately treated as an investment, which is axiomatic in closed economies.…”
Section: Resultsmentioning
confidence: 99%
“…It can therefore be concluded that the initially lower level of development is conducive to higher dynamics of GDP growth. The variables found in the second and third positions of the ranking, that is, X 2 , gross national savings, and X 12 , gross fixed capital formation, respectively, refer to a similar subject, which can have a considerable impact on the dynamics of economic growth, both theoretically and in practice (Matuzeviciute and Butkus [69], Danileviciene and Lace [70]). Gross fixed capital formation directly demonstrates the proportion of GDP that is further invested, and the gross national savings, understood in the Keynesian approach, can be also ultimately treated as an investment, which is axiomatic in closed economies.…”
Section: Resultsmentioning
confidence: 99%
“…Many studies address the organizations' sustainable performance and openness to innovation as important requirements for continuous development [5,6,68]. Some authors focus on implementation of standards or total quality management practices as the foundation for building an organizational environment appropriate for implementing innovations [65].…”
Section: Conclusion Discussion and Further Studiesmentioning
confidence: 99%
“…There is a wide range of ways how organizations could measure their performance regarding sustainability. Many studies address the organizations' sustainable performance and openness to innovation as important requirements for continuous development [5,6]. It also depends on what level of performance the organization is looking at-organizational, process or performer level [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fields the entrepreneurs represented were manufacturing, business consulting, IT, and interior design. While the sectors of economy do not make a great impact on the dynamics of the domestic GDP and are not as productive as construction or electricity supply industries [66], development of the right skills set could significantly improve the productivity of an enterprise. One competence was separately distinguished from the EntreComp list, namely, activating the market which is the ability to be able to create demand for the product, to be knowledgeable about the market and to use this knowledge for the benefit of the start-up.…”
Section: Latviamentioning
confidence: 99%